Clinicopathological Implication of HER2/neu Expression in Carcinoma Stomach - Asnani, Ritu; Shetty, Padma K.; Shetty, Vijith V.; Patil, Prakash; Shetty, Jayaprakash K. (Journal of Health and Allied Sciences NU, 2024)
Background and Objectives Metastatic gastric carcinoma makes the current treatment options unsatisfactory. There is HER2 directed therapy like transtuzumab are used in metastatic gastric cancer. This study aimed to determine the tissue HER2/neu status by immunohistochemistry (IHC) and find their relation with clinicopathological parameters for assessing the prognosis.Study Design, Materials, and Methods In this descriptive study, 30 patients of gastric cancer with metastasis were studied for HER2/neu expression by IHC. The chi-square test was used to determine the association between HER2/neu expression and clinicopathological parameters of patients.Results and Conclusion The majority of samples (90%) were endoscopic biopsies from patients with a mean age of 61.4 years. Tumors were majorly of intestinal type (67%) with moderately differentiated grade located at the fundus of the stomach. The common site of metastasis was the lymph node (53.33%) followed by lymph node and liver metastasis (13.33%). The overexpression of HER2/neu by IHC was observed in 13.3% of cases. Furthermore, no significant association was observed between HER2/neu and gender, diet, age, tumor site, subtype, and grade. Overall, HER2/neu overexpression can be considered an independent prognostic factor for carcinoma stomach. Therefore, the patients identified with HER2/neu overexpression are targeted for trastuzumab therapy.
Keywords: gastric carcinoma; HER2/neu; immunohistochemistry; metastasis; trastuzumab